The Influence of Audio Visual Media on Increasing Student Learning Motivation in Islamic Education Learning at SMP Negeri 1 Pangarururan - Simarmata, Sarma; Tanjung, Maimunah; Simamora, Anni Teresia (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to Motivate student learning in Islamic religious education learning using Audio Visual Media. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning motivation and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. the results of the study indicate that Audio Visual Media can Motivate student learning in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle increased to 90.32%. Thus, the use of Audio Visual Media can be used as an alternative to Motivate student learning in Islamic religious education learning.